Cold Tolerance of Photosynthetic Electron Transport System Is Enhanced in Wheat Plants Grown Under Elevated CO2 - Zhu, Xiancan; Liu, Shengqun; Sun, Luying; Song, Fengbin; Liu, Fulai; Li, Xiangnan (Frontiers in Plant Science, 2018)
The effects of CO2 elevation on sensitivity of photosynthetic electron transport system of wheat in relation to low temperature stress is unclear. The performance of photosynthetic electron transport system and antioxidant system in chloroplasts was investigated in a temperature sensitive wheat cultivar Lianmai6 grown under the combination of low temperature (2 days at 2/-1 ºC in the day/night) and CO2 elevation (800 μmol l-1). It was found that CO2 elevation increased the efficiency of photosynthetic electron transport in wheat exposed to low temperature stress, which was related to the enhanced maximum quantum yield for electron transport beyond QA and the increased quantum yield for reduction of end electron acceptors at the PSI acceptor side in plants under elevated CO2. Also, under low temperature, the activities of ATPases, ascorbate peroxidase and catalase in chloroplasts was enhanced in wheat under elevated CO2. It suggested that the cold tolerance of photosynthetic electron transport system is enhanced by CO2 elevation.